Evaluasi Penjadwalan Waktu Proyek Pembangunan Gedung Menggunakan Critical Path Method (CPM) - Annisaa Dwiretnani; Elvira Handayani; Niko Saputra (Jurnal Talenta Sipil, 2023)
Buildings are the physical form of the results of construction work that are integrated with their place of domicile, partly or wholly located on and/or in the land and/or water which functions as a place for humans to carry out their activities, both for housing (residence), religious activities, business activities, social activities, culture, and special activities (Article 1 Number 1 Law Number 28 of 2002 Concerning Building Buildings). The success or failure of a construction project is influenced by three aspects, namely costs that do not exceed the budget, quality according to specifications and time according to the implementation schedule. The existence of project time scheduling is needed to complete the project in a timely manner using several methods. This study aims to create a network for building construction projects using the Critical Path Method (CPM) and identify any work activities from building construction projects that are on a critical path. Research data only consists of secondary data in the form of project time schedules and documentation photos. Based on the analysis, it is known that there are 11 types of work that are on the critical path network of the Abdul Manap Hospital Inpatient Building Development Project in Jambi City using CPM analysis, which consists of AA (Preparatory Work) – BA (Work on Structure 1st Floor) – BB (Work on Structure 2nd Floor) – BC (Work on Structure on 3rd Floor) – BD (Work on Structure on 4th Floor) – BE (Work on Structure on Floor 1) – DF (Installation of Dirty Water, Used Water & Vent) – DA (Work on Structures on 4th Floor) Air Conditioning work) – DO (Lightning Protection Work) – FF (Chopstick Work) – FG (Parking and Greening Work). The total duration/time of completion of all work on the critical path is 240 days.